Citação e alusão nas crônicas machadianas: estratégias de ler e escrever pelo avesso - Santos, Erivaldo dos (2010)
This dissertation deals with the quotations and allusions found in Machado s chronicles. This study focuses on the circuit of the Sermon on the Mount as a reading and writing strategy in the process of alluding and quoting; its rewriting strengths are found in inversion through irony or parody in tune with the seriocomic Lucianic lineage. Five chronicles were selected for the body of this research, namely: "Parasite II" in the "Watercolors" section of October 9th, 1859, published in The Mirror newspaper; the chronicles published in the "By chance" section of June 12nd, 1864 and 22 August 1864, in the Rio de Janeiro newspaper, and besides these, two more chronicles from September 4th , 1892 and March 25th , 1894, which were published in the " The Week" section of the Gazeta de Noticias newspaper. We raised the following question as the central issue of this study: how does Machado de Assis make use of quotations and allusions, thus emptying the canonical discourse and revealing its anti-dogmatism? We hypothesize that the use of quotations and allusions is Machdo s method of reading and writing inside out, which is based on irony and parody, so as to empty the canonical discourse of the biblical tradition, represented by the Sermon on the Mount. Our research was guided by the theoretical support on the readable and writeable text of Barthes and parody grounded in Linda Hutcheon and Bakhtin, in addition to the studies of Enylton de Sá Rego regarding the link of Machado's work with the Menippus satire genre of Lucianic lineage. After reading, analyzing and comparing the quotations and allusions of the Sermon on Mountain in selected chronicles, we believe that Machado de Assis makes uses of quotations and allusions, albeit in a lesser degree, a genre called chronicle, as the discursive strategies that aim at training the reader